Strategi Guru Pendidikan Agama Islam dalam Meningkatkan Kemampuan Membaca Al-Quran bagi Peserta Didik di SMK Negeri 1 Batangtoru - Rizky Rhamadan; Al- Ikhlas (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This research was conducted to find out how the PAI strategy is to improve students' Al-Quran reading skills, including students' Al-Quran reading skills, teacher strategies, supporting and inhibiting factors for teachers, as well as the results of Al-Quran reading strategies. The method used by researchers in this research is qualitative with a descriptive approach. This research was conducted at SMKN 1 Batangtoru. Data collection techniques used are observation, documentation and interviews. The findings show that students' ability to read the Koran varies for each individual. As for the teacher's strategy, such as getting used to reading the Koran before PAI learning begins, grouping students, and applying reading and listening to the Koran. The methods used, such as the iqro, amma, sas, qiroati, and tahsin methods. While the supporting factors for the teacher's strategy include the role of the principal, the role of parents, the extracurricular recitations, and the high level of motivation of students in participating in learning the Koran and the inhibiting factors for the teacher's strategy include the lack of books on learning the Koran, the lack of time for PAI learning, and lack of learning media facilities. The results obtained by students after receiving Al-Quran learning were gradually increasing.